Artist Bảo extended interview - Son Nguyen (22474540) (2025)
Video of Co-I Phạm Thanh Thôi interviewing Artist Bảo. Topics include his artistic training, mentor, career trajectory to date including his decision to invest in the first printing machine in his home province of Long Xuyên, family life, Vietnam's advertising landscape, his future plans and hopes for the profession.